Capsaicin suppressed activity of prostate cancer stem cells by inhibition of Wnt/β‐catenin pathway. (28th November 2019) - Zhu, Mingming; Yu, Xi; Zheng, Zongmei; Huang, Jiaming; Yang, Xuepan; Shi, Hongfei
Abstract: Cancer stem cells (CSCs) are considered as the origin and driving cells of cancer, and play a key role in the progress of cancer. Studies have shown that capsaicin exerted inhibitory effect on prostate cancer cells, however, the effects of capsaicin on prostate CSCs remain undefined. In the present study, we showed that capsaicin could downregulate prostate CSCs markers and inhibit the growth of PC‐3 and DU145 prostate cancer stem cells. Further, we found capsaicin suppressed the expression of Wnt‐2, p‐GSK3β and β‐catenin, along with downregulation of Wnt/β‐catenin pathway target genes c‐myc and cyclinD1. Using LiCl, a activator of Wnt/β‐catenin pathway, we found activation of Wnt/β‐catenin pathway could ameliorate the downregulation of prostate CSCs markers and the growth inhibition induced by capsaicin in prostate cancer stem cells. Those data suggested that the inhibition effect of capsaicin on prostate cancer stem cells and the anti‐cancer effect of capsaicin on prostate cancer stem cell may be mediated by Wnt/β‐catenin pathway. Findings from this study reveals for the first time the potential role and mechanisms of capsaicin on prostate cancer stem cells.